2012
DOI: 10.1007/s10562-012-0775-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photocatalytic Conversion of Tryptophan to Kynurenine Using Black Light as a Light Source

Abstract: The photocatalytic conversion of an aqueous solution of L-tryptophan (Trp) to kynurenine (KN) was investigated under the illumination of different light sources. Results show that Trp converted to KN with a selectivity of 64% under the illumination of a medium pressure (MP) Hg lamp. KN selectivity was increased to [90% when black light (BL) was used a light source. The novel use of BL in the photocatalytic conversion of Trp to KN significantly reduces the energy consumption compared with MP light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…161 Alternatively, TiO 2 can be used to photo-deformylate tryptophan into kynurenine under black light with up to 90 mol% selectivity. 162 Kynurenine can be used to produce alanine and, by further decarboxylation over zeolite catalysts, bio-based aniline. 163 …”
Section: Titanium Dioxide Photodecarboxylationmentioning
confidence: 99%
“…161 Alternatively, TiO 2 can be used to photo-deformylate tryptophan into kynurenine under black light with up to 90 mol% selectivity. 162 Kynurenine can be used to produce alanine and, by further decarboxylation over zeolite catalysts, bio-based aniline. 163 …”
Section: Titanium Dioxide Photodecarboxylationmentioning
confidence: 99%
“…Other studies have demonstrated that these metabolites are major ultraviolet-photooxidation products of tryptophan (76). Hamdy et al exposed tryptophan to various light sources and demonstrated that UVB light markedly increased metabolism along this pathway (77). Sheipouri et al have shown that UV skin damage correlates with production of kynurenines from tryptophan (78).…”
Section: Tryptophan Fluorescencementioning
confidence: 99%
“…23 The photocatalytic decomposition of tryptophan has also been reported to produce kynurenine. 24 In 2006, Ferrini et al 25 reported the preparation of 2-aryl amines in high yields by photochemical rearrangement of aromatic amides when they were irradiated with UV light. Cbz-tryptophan has been used to prepare L-kynurenine upon reaction with the oxidizing mixture of DMSO/HCl in AcOH, followed by additional oxidation with air (Scheme 2F).…”
Section: Paper Synthesismentioning
confidence: 99%